The intergenerational elasticity of earnings: Exploring the mechanisms - Uta Bolt; Eric French; Jamie Hentall-MacCuish; Cormac O'Dea (The Institute for Fiscal Studies (IFS), 2024)
How do education, skills, investments of parental time and school quality, and family circumstances during childhood contribute to the persistence of earnings across generations? Building on a classic literature in sociology and a more recent literature in economics, our model allows each of the above variables to affect lifetime earnings directly, as well as through their contribution to human capital formation. The model allows us to decompose the intergenerational elasticity of earnings (IGE) into its drivers. Using data from a representative British cohort followed from birth to age 55, we show the above variables explain most of the IGE. A key driver is the increased levels of parental investments received by children of high income parents early in their lives, and the resulting cognitive development.
Keywords: I24; J24; C38; 330; Parental Investments; Cognitive Skills; Intergenerational Elasticity of Earnings